2021
DOI: 10.1111/ijd.15494
|View full text |Cite
|
Sign up to set email alerts
|

Circulating long noncoding RNA growth arrest‐specific transcript 5 as a diagnostic marker and indicator of degree of severity in plaque psoriasis

Abstract: Background The current study aims at evaluating the role of circulating or cell‐free long noncoding ribonucleic acid (lncRNA) growth arrest‐specific 5 (GAS5) in plaque psoriasis and at investigating its relationship with the presented clinical data. Methods This case‐control study was conducted on 180 subjects, divided into two main categories as follows: 90 cases with plaque psoriasis and 90 age‐ and sex‐matched healthy controls. Full history taking, thorough general examination, and full dermatological exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…LncRNAs have been revealed to participate in the pathogenesis of psoriasis, including MEG3, GAS5, and MIR31HG ( Gao et al, 2018 ; Jia et al, 2019 ; Ahmed Shehata et al, 2021 ). Here, we demonstrated that KLHDC7B-DT positively regulates the proliferation of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been revealed to participate in the pathogenesis of psoriasis, including MEG3, GAS5, and MIR31HG ( Gao et al, 2018 ; Jia et al, 2019 ; Ahmed Shehata et al, 2021 ). Here, we demonstrated that KLHDC7B-DT positively regulates the proliferation of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA-RP6- 65G23.1 is a significant upregulated lncRNA in psoriasis that promotes keratinocyte proliferation and suppression of apoptosis by modifying the expression of Bcl-xl, Bcl2 and the ERK1/2-AKT signaling pathway [ 86 ]. Other upregulated lncRNA in psoriasis are MIR31HG [ 87 ], MSX2P1 [ 88 ], XIST [ 89 ], FABP5P3 [ 90 ], KLDHC7B-DT [ 91 ], or SPRR2C [ 92 ]; whereas, MEG3 [ 93 ], GAS5 [ 94 ], PRINS [ 95 ] or NEAT1 [ 96 ] are downregulated in psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the schematic in Figure 1, there are eight conventional lncRNAs regulatory mechanisms: (1) transcription interference involving transcription from the upstream promoter region of a target protein-coding gene (Figure 1A); (2) inhibiting RNA polymerase II or inducing chromatin remodeling or histone modification, which interferes with target gene transcription (Figure 1B); (3) generating complementary double strands involving mRNAs, which interferes with mRNA cleavage (Figure 1C); (4) generating endogenous short interfering RNAs (endo-siRNAs), which target specific mRNAs (RNA interference) (Figure 1D); (5) binding to a specific protein to modulate its activity (Figure 1E); (6) forming a ribozyme-protein complex, which catalyzes specific reactions (Figure 1F); (7) binding to a specific protein to alter its cellular localization (Figure 1G); and (8) producing small RNA precursors (Figure 1H). Some upregulated lncRNAs play a tumor-promoting role, while downregulated lncRNAs in gastric cancer play a tumor-inhibitory role (Figure 1B) (Ahmed Shehata et al, 2021). Some lncRNAs can regulate protein activity (Figure 1C).…”
Section: Conventional Lncrnas Regulatory Mechanismmentioning
confidence: 99%